Standardization of an efficient DNA isolation protocol in tannia [Xanthosoma sagittifolium(L.) Schott] - A. Asha Devi; Ann P. George; N. Krishna Radhika; Shirly Raichal Anil; K.I. Asha (JOURNAL OF ROOT CROPS, 2024)
Genetic variability is very much limited in tannia (Xanthosoma sagittifolium(L.) Schott).Morphological variation is limited to colour variation in leaf, petioleand tuber flesh colour in this crop. Tuber shape and size also shows variation. ICAR-CTCRI being the National Repository for tuber crops is maintaining the germplasm collection of edible aroids including tannia. In order to assess the genetic diversity existing in this introduced crop, different DNA isolation protocols were tested in four tannia accessions to identity the best method. CTAB method standardised by Sharma et al., (2008) for taro, DNeasy kit method (Qiagen) and modified Dellaporta method were tried. It was observed that the quality of DNA was good in the modified Dellaporta method with DNA quality ranging from 1.98 (Xa-6) to 2.23 (Xa-67). Good quantity was obtained ranging from 830 ng/?l (ACIX-2) to 1968 ng/?l (Xa-71). The extracted DNA was amenable to ISSR markers. Hence, for all further molecular studies in tannia, the modified Dellaporta method was adopted.